الحق في الرعاية الاجتماعية للأشخاص المسنين على ضوء التشريع الجزائري - سعدودي, يوسف; عمروش, حسين (جامعة الوادي University of Eloued, 2019)
حضي الحق في الرعاية الاجتماعية للأشخاص المسنين بالجزائر باهتمام واسع، وتجلى هذا في نصوص قانونية عديدة : كالدستور، قانون الأسرة، قانون العقوبات، قانون حماية الأشخاص المسنين. وتعزيزا لحق الأشخاص المسنين في الرعاية الاجتماعية تضطلع مؤسسات الدولة خاصة دور الأشخاص المسنين بالتكفل الاجتماعي بالأشخاص المسنين بدون روابط أسرية، بحيث يستفيد الأشخاص المسنين من خدمات أخرى كالمساعدة في المنزل، اللجوء إلى أسلوب الوساطة العائلية والاجتماعية والوضع لدى عائلات الاستقبال. تضمن الدولة الجزائرية للأشخاص المسنين المساعدات المالية كالمنحة الجزافية للتضامن، وبعض الامتيازات كالنقل أو التخفيض في تسعيرته والاستفادة من نظام الأولوية في المرافق العمومية،كما يتم تقديم مساعدات عينية خاصة كالأجهزة الطبية والأدوية التي تتطلبها الحالة الصحية للشخص المسن . الكلمات المفتاحية:الرعاية الاجتماعية، الأشخاص المسنيين، التشريع الجزائري، الدستور، قانون حماية الأشخاص المسنين. key words: social care, the elderly, Algerian legislation, the constitution, the Law of elderly protection. Abstract : The right in social care for the elderly in Algeria has been a subject of interest on a large scale. That is justified by the multiple judiciary texts in the constitution, the Family Code, the Penal Code and the law of the elderly protection, . . . To harness the right of the elderly in social care, the institutions of the government, mainly the nursing home care, took over the welfare of the elderly without family ties . Each individual benefits from other services like home care and family mediation as well as placements within host families. The Algerian government insures financial aids for the elderly like solidarity grant and other privileges like free transportation or discounts, along with benefiting from priority in public utilities. Other financial aids granted like medical materials and drug that elderly medical state. key words: social care, the elderly, Algerian legislation, the constitution, the Law of elderly protection.
The Right To Social Welfare Of The Elderly In The Light Of Algerian Legislation
Keywords: الرعاية الاجتماعية،الاشخاص المسنيين، التشريع الجزائري، الدستور، قانون حماية الاشخاص المسنيين; socil car, the elderly, Algerian legislation, the constitution, the law of elderly protectionslation, the constit